Krzysztof Penderecki’s Eighth Symphony, ‘Lieder der Vergänglichkeit’ - from inspiration by nature to existential reflection - Chłopicka, Regina (Interdisciplinary Studies in Musicology, 2018)
In the Penderecki oeuvre, symphonic music has been pivotal, with eight symphonies written over the span of forty years, including Symphony No. 6, which remains in the sketch stage. As he admits, the sequence of symphonies constitutes a sort of musical autobiography. In the life and work of Penderecki his interests in nature and culture have long run parallel, and in both spheres the moment of creation has been particularly significant. Penderecki’s artistic work has clearly focused on two domains: composing music and moulding the nature which surrounds his Luslawice house - the space of the garden and park. The latter type of art concerns nature not in its primeval form, but rather in the shape imposed on it by man. Over the last decade, the composer’s two passions have tended to drift closer together and intertwine. During this time, he has written his Eighth Symphony (‘Lieder der Vergänglichkeit’), devoted to trees, and Three Chinese Songs, permeated by his enchantment with the beauty of nature. In his Eighth Symphony, Penderecki employs poetic and musical images to show the beauty and diversity of the forms of the surrounding world of nature, in which it is given to man to live the successive phases of his life. However, a relevant dimension of the symphony is that of looking from a distance at the fate of man - the existential reflection offered mainly by the commenting choral parts, as in ancient tragedy. What dominates is a sense of transition, the sadness of decline and the thought of the inevitability of the fate of man, who searches for a way to unravel the mystery of existence.